Boosting Teacher Productivity: Effective Stress Management for Teachers in Public Secondary Schools in Kwara State, Nigeria - Abigail Oluyemisi Fadare; Olaolu Paul Akinnubi; Clement Aliu Ogbaini (Suluh: Jurnal Bimbingan dan Konseling, 2024)
The productivity of teachers in public secondary schools is vital for common educational development. However, the traumatic nature of the coaching career frequently results in high tiers of pressure amongst educators which could considerably affect their performance and well-being. Therefore, it's miles imperative to put into effect powerful pressure management strategies to assist teachers in improving their productivity and maintaining a healthful work-life balance. This observation investigates the diverse stressors faced by teachers in public secondary colleges in Kwara State, Nigeria and explores the effect of stress on their productivity. Additionally, the paper examines present-day stress control practices and their effectiveness in assuaging the weight of pressure amongst educators. Identifying effective strategies for mitigating pressure, takes a look at goals to enhance teacher productivity and ultimately enhance the great of education in Kwara State. In the end, developing comprehensive guide structures that prioritize the proper well-being of educators lays the inspiration for an extra effective and thriving instructional environment in Kwara State.